The rise and decline of the textile weaving industry in Miag-ao, Iloilo (1900s-1980s) - Nieves, Nelcy C.
The study discussed the changes that resulted from the rise and decline of the textile weaving industry in Miagao, Iloilo. Specifically, the study tackled the origin and the factors that5 led to the rise of the industry, the effects of the industry?s development, the products, materials and techniques involved in textile weaving, the reasons and effects of the decline. Textile weaving in Miagao, Iloilo was believed to have started as early as the first settlement of Miagaowanon in the place was abundant of wildly grown raw materials like bamboo, sibukaw2, and cotton which paved the way for the rise of the industry. Moreover, it flourished because families relied very much on it for their clothing needs and also to earn income. In the 1930s, Miagao?s textile weaving industry experienced a remarkable degree of progress. People from other towns and provinces came to Miagao to engage in the textile weaving industry either as capitalista or simply as consumers. Among Miagao?s woven products, the ones that were popular were the patadyong and mosquito nets and later years blankets, pillow cases, hankies and tablecloths. Textile weaving was the most important industry of Miagao especially among its women, as it was also important to the socio-cultural and economic life of the municipality. The town became a ?textile weaving center? in Southern Iloilo despite the competition pose3d by machine-made textile and other booming industries like sugar production. The greater emphasis placed on education and increase in the number of the Miagaowanon dollar-earners were among the socio-economic changes in the 1930s to the 1980s. Yet, the said industries and socio-economic changes caused the industry?s decline by the early 1980s. Since it was very important to the economic life of Miagao as it earned a good income for the family and municipality its decline in the 1980s was a great loss for the Miagaowanons. The textile weaving industry of Miagao was one of the important traditions the Miagaowanons can be proud of.